Polyhydroxyalkanoates as biomaterials (vol 8, pg 1774, 2017) - Gadgil, Bhagyashri S. Thorat; Killi, Naresh; Rathna, Gundloori V. N. (MedChemComm, 2019)
Correction for `Polyhydroxyalkanoates as biomaterials' by Bhagyashri S. Thorat Gadgil et al., Med. Chem. Commun., 2017, 8, 1774-1787.